HYDROLYSIS OF CARBOHYDRATES IN CASSAVA PULP AND TAPIOCA FLOUR UNDER MICROWAVE IRRADIATION - Euis Hermiati; Jun-ichi Azuma; Djumali Mangunwidjaja; Titi C. Sunarti; Ono Suparno; Bambang Prasetya (Universitas Gadjah Mada, 2011)
Cassava pulp and tapioca flour are potential sources of glucose. In this work, validity of microwave irradiation for hydrolysis of carbohydrates, especially starch, present in cassava pulp and tapioca flour was estimated as a non-enzymatic saccharification technique. Suspension of cassava pulp or tapioca flour in distilled water (1g/20 mL) was subjected to microwave irradiation at temperatures of 140-240 °C with pre-heating time of 4 min and heating time of 5 min. Solubilization rate of cassava pulp increased with increasing temperature of microwave heating treatment and reached maximum (92.54%) at 220 °C, while that of tapioca flour reached almost 100% at 140 °C. Production of malto-oligomers from starch in cassava pulp and tapioca flour was clearly observed at 220 °C. The highest glucose yields from cassava pulp and tapioca flour in this experiment were 28.59 and 58.76% dry matter, respectively. Variation of pre-heating time at 230 °C did not give significant effects on glucose yield from cassava pulp. However, glucose yield from tapioca flour decreased due to increase of pre-heating time. Microwave irradiation is a promising method of hydrolysis for cassava pulp and tapioca flour due to the fast process.